Hygrothermal modelling as a top-down design tool for mesoporous desiccants - Sarce Thomann, Fernando (2016)
When considering targeted regulation of transient response to changes in relative humidity within closed environments, selection of a material’s suitability requires fundamental understanding of its hygrothermal functional properties as well as the morphology of mesoporous materials. The overall aim of this research was to develop a top-down design technique using hygrothermal modelling simulations that enabled the design of mesoporous desiccants materials. This technique was used to inform the specification of optimized hygrothermal properties with the intention to enhance regulation of any relative humidity buffering application within closed environments. In order to accomplish this, a series numerical simulations using as a template pre-existing mesoporous desiccants properties data were performed. It was found that the linear portion of the hypothetically-created water vapour isotherms correlated with the rate of decline in adsorption/ desorption. This was found to be highly sensitive to the moisture content gradient, Δw between the upper and the lower relative humidity limits of the water vapour adsorption isotherm. The stages of the kinetics of water vapour adsorption found consistent agreement with the moisture content gradient and the exchange rates for moisture loads. This assisted the design process for newly created mesoporous solids (MCM-41 and SBA-15) when informing the optimized hygrothermal properties with respect to targeted relative humidity buffering applications. The latter enabled the quantification of the relative effect on energy efficiency (latent heat) when assisting an HVAC system as a dehumidifier. The major implication of this research was the novel theoretical insight that enabled a top-down predictive design using hygrothermal numerical modelling. This allowed functional properties optimization for mesoporous solids with respect to specific targeted closed environments, by informing material’s preparation via enhanced modulation of ‘ideal’ pore geometry.